Your child's first pet: Some advice from the American Academy of Pediatrics. (December 2015) - Knopf, Alison
Abstract : There are so many reasons for having pets around the house, especially if you have children as well. The family dog, the cats cuddling on the couch, the chirping parakeet — all become a part of the family. But what about actually making your child be the main owner of the pet? That has its definite benefits: a great companion, plus a way to learn responsibility. But before you do this, the American Academy of Pediatrics has some important recommendations.